CONTRIBUTION OF SAVING AND CREDIT COOPERATIVES ON HOUSEHOLD POVERTY REDUCTION IN KONGUNGA TOWN COUNCIL, BUKEDEA DISTRICT LOCAL GOVERNMENT - OCHEKA PAUL (My University, 2024)
ABSTRACT The study sought to find out the effect of village savings and loan associations on household economic welfare in Kongunga Town Council, Bukedea District. The study was guided by the research objectives which included examining the contribution of loans on Household Poverty Reduction, assessing the contribution of savings on Household Poverty Reduction and establishing the contribution of financial literacy trainings on Household Poverty Reduction. The study used a mixed research approach where descriptive research design was used. A sample size of 109 respondents was used and simple random sampling as well as purposive sampling methods were used to select respondents for the study. The researcher used Questionnaires and interview guide for data collection and data was analyzed using SPSS. The findings revealed that education of the children was made possible through loans acquired, opening up of the business entities is through loan provision and family income has increased and acquisition or hiring of new manpower is realized through provision of loans. Consultancy services are capable of boosting welfare of households as it enables prompt and efficient access to reliable financial data and helps strengthen financial controls, improving the provision of government services, raising the budget process to higher levels of transparency and accountability. The findings reveal that SACCOs educate clients on how and to where to invest loans, SACCOs give loans to clients who have saved more gifts, and SACCOs use measures to communicate and remind clients to pay the loans when they default. In conclusion, the findings show that loans were disbursed when all requirements are met, income levels of customers were considered when giving a loan, and SACCOs provide clients with a loan repayment schedule and that SACCOs teach people on how to open up an account, SACCOs educate the clients on how to use loans obtained, and SACCO have motivating factors that help members to save more. The researcher recommends that Village savings and loans associations need to continue encouraging clients to save more in order to improve on their household income, and that they need to consider income levels of customers before giving them a loans as this may minimize on loan defaulting. They also need to continue educating clients on how and where to invest loans in profitable ventures.